Diagnostic and Therapeutic Methods of Atypical Pneumonia in Children - Ibragimova Marina Fedorovna; Khusainova Shirin Kamiljonovna; Rasulova Nadira Alisherovna (Genius Journals, 2022)
Diagnosis and treatment of atypical community-acquired pneumonia in children is a topical issue in pediatric practice. Pneumonia today is one of the most common diseases of childhood, which occupies one of the main places of morbidity and mortality. Among the primary causes of poor outcome of pneumonia in children is late diagnosis and inadequate therapy. To optimize treatment, in order to differentiate typical or atypical etiology of community-acquired pneumonia, we performed polymerase chain reaction (PCR), express methods for determining the level of procalcitonin and C-reactive protein in blood plasma in children. And thanks to the responses, they were treated with antibacterial and antiviral drugs. We have treated 80 patients aged 2 to 14 years who were divided into 2 groups. The patients were hospitalized in the departments of emergency pediatrics and the pediatric intensive care unit of the Samarkand branch of the Republican Scientific Center for Emergency Medical Care. 40 patients underwent complex therapy, which included an antibacterial drug, antiviral drugs at an age dosage for 10 days. Clinical manifestations of group I stopped almost 1.5 times faster than in patients from group II. The complex treatment of community-acquired pneumonia with atypical etiology with an antibiotic and an antiviral drug showed that they are the most effective, preventing and reducing the severity of the disease
Keywords: diagnosis; treatment; atypical pneumonia; children